Environmental factors, urbanization and aging - Mena Cabrera, Yamaris Mercedes; Herrera Gómez, Oralis; Cabrera Mejico, Damarys; Díaz Pita, Gicela; Acosta Martínez, Lazara Yumerci (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Population aging is an undeniable reality, it is estimated that the average age of rural populations will increase more than in urban areas. Objective: to characterize environmental factors, urbanization and aging in the community of the Luis Augusto Turcios Lima polyclinic of Pinar del Río, in the period from January to July 2022. Method: An observational, analytical and transversal study was carried out; the universe was constituted by 432 older adults belonging to medical offices 53 and 64 of the polyclinic, a sample of 361 was selected, by intentional non-probabilistic sampling. Theoretical and empirical methods were used, including the review of the individual clinical history and the Health Situation Analysis of each medical office and descriptive statistics. Results: The predominant age group was 65 to 69 years (medical office 53: 48.81% and medical office 64: 49.63%), female sex: (medical office 53: 37.51% and medical office 64: 39.63%), the most frequent non-communicable chronic diseases were: Arterial Hypertension, Diabetes Mellitus and Cerebrovascular Disease (63.7%: 56.3%, 38.9% in medical office 53 and 60.2%, 59.4% and 35.3% in medical office 64). Conclusions: accessibility to medical services, prevention and control of environmental factors, compliance with the program of care for the elderly guarantee a similar aging in Cuba for any geographical location.